2004
DOI: 10.1073/pnas.0400375101
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the periplasmic component of a bacterial drug efflux pump

Abstract: Multidrug resistance among Gram-negative bacteria is conferred by three-component membrane pumps that expel diverse antibiotics from the cell. These efflux pumps consist of an inner membrane transporter such as the AcrB proton antiporter, an outer membrane exit duct of the TolC family, and a periplasmic protein known as the adaptor. We present the x-ray structure of the MexA adaptor from the human pathogen Pseudomonas aeruginosa. The elongated molecule contains three linearly arranged subdomains; a 47-Å-long ␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
252
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(262 citation statements)
references
References 36 publications
10
252
0
Order By: Relevance
“…In the simplest interpretation, our results suggest a single binding site on the TolC protomer, interacting with the ␣-helical hairpin of a single adapter molecule. We saw no evidence for interaction with residues facing the TolC monomer interface on helices H3/H4/ H7* with any of the cross-linking agents, but weaker secondary contact sites cannot be excluded especially as ITC data indicate concentration-dependent binding events (6), and physically there would appear to be space to accommodate up to three adaptor subunits per TolC monomer (18,20).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the simplest interpretation, our results suggest a single binding site on the TolC protomer, interacting with the ␣-helical hairpin of a single adapter molecule. We saw no evidence for interaction with residues facing the TolC monomer interface on helices H3/H4/ H7* with any of the cross-linking agents, but weaker secondary contact sites cannot be excluded especially as ITC data indicate concentration-dependent binding events (6), and physically there would appear to be space to accommodate up to three adaptor subunits per TolC monomer (18,20).…”
Section: Discussionmentioning
confidence: 85%
“…A possible explanation of this is that the TolC coordinates used for the AcrA docking are those of the closed form and the observed space allows the movement of the TolC inner coiled-coil during transition to the open state. Consistent with such a key role, a number of these residues, particularly those directed toward TolC, are conserved in the AcrA protein family (18). To test this possibility, we simulated the opening in the docked complex by forcing movement of the lower region of the TolC inner coiled-coil (from residue Ala 347 to Ala 382 , Fig.…”
Section: Modeling the Tolc-acra Coiled-coil Interface In Closed And Openmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 11 RND efflux pumps identified in this organism, 10 pumps, MexAB-OprM (Poole et al, 1993), MexCD-OprJ (Poole et al, 1996), MexEF-OprN (Kohler et al, 1997), MexGHI-OpmD (Aendekerk et al, 2002;Sekiya et al, 2003), MexJK (Chuanchuen et al, 2002), MexMN (Mima et al, 2005), MexPQ-OpmE (Mima et al, 2005), MexVW (Li et al, 2003), MexXY (Mine et al, 1999;Westbrock-Wadman et al, 1999) and TriABCOpmH (Mima et al, 2007), have been experimentally confirmed, and their properties have been reported. The RND-type efflux pump usually consists of three components to fulfil the function properly and includes an innermembrane component (RND component), a periplasmic component (MFP component), and an outer-membrane component (OMP component) (Touze et al, 2004), and the three-dimensional structures of MexA, MexB and OprM have been reported (Akama et al, 2004a, b;Higgins et al, 2004;Sennhauser et al, 2009). However, regarding the most recently analysed RND efflux pump in P. aeruginosa, TriABC-OpmH, it has been reported that this system needs four components: an RND component, two MFP components and an OMP component (Mima et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The energy source for drug transport is derived from the proton motive force and these transporters function as drug/proton antiporters. For all 3 individual components, structural information based on X-ray crystallography is available (4)(5)(6)(7)(8)(9)(10)(11) and has led to several suggestions of tripartite pump assemblies (10-13) (Fig. 1).…”
Section: Cluster Of Excellence Macromolecular Complexes and Institutmentioning
confidence: 99%